(untitled) (Journal of Agriculture & Rural Development, 2010)
The experiment was conducted with 24 accessions of pointed gourd at the Regional Agricultural Research Station, Ishurdi, Pabna during the growing season 2005-2006. Evaluation of 24 accessions of pointed gourd for yield and yield components reveled high phenotypic and genotypic coefficients of variation (PCV and GCV, respectively). Wide variations among the accessions in respect of plant, leaf, flower, fruit and seed characters were recorded. The accessions varied significantly for days required to first flowering, number of node at 1st harvest, inter node length at first harvest, vine length at 1st harvest, fruit length, fruit breath, fruit weight, pulp weight per fruit, pulp seed ratio, number of fruits per plant, weight of fruits per plant, number of seeds per fruit, weight of seed per fruit and yield. Key words: PVC; GVC; Correlation; Path Analysis; Pointed gourd. DOI: 10.3329/jard.v7i1.4427 J Agric Rural Dev 7(1&2), 93-98, June 2009